International Free Trade: Can Indonesia Survive It? - Ahmad Idris Asmaradhani (BALANCE: Economic, Business, Management and Accounting Journal, 2007)
There have been arguments that, for Indonesian economic development, competitive advantage will soon replace comparative advantage. It is also argued that one country should not be satisfied with its comparative advantage. As a cpuntry who has enjoyed comparative advantage for about three decades, Indonesia must not be a country that exports labour-intensive commodities forever. It must shift to being a country that exports capital-intensive and high skill intensive commodities. It must also find which commodities are going to be competitive in the world market. A skepticism stems from the fact that the developing countries usually specialize in agricultural products, while the developed countries specialize in manufacturing products. It is also argued that with the current open international free trade, the products of the developing countries will not be able to compete with those from the developed countries.  Key phrases: free-trade, labor-force, traditional industries